Opportunities for Hosting Mega Sports Events (Case Study: Qatar) - Yousef Mostafa, Nawfel; Dousti, Morteza; Tabesh, Saeed; Farzan, Farzam (Iranian Journal of Educational Sociology, 2022)
Purpose: The current research aimed to identify the opportunities of hosting mega sports events (case study: Qatar). Methods and Materials: interpretive paradigm, qualitative approach, and foundational data theorizing strategy were utilized with an emergent or Glazerian approach. The research participants were experts in sports events, such as sports managers, sports management professors, sports experts, and experienced athletes participating in international events. The theoretical sampling method was purposeful, and the persons were consciously selected. The semi-structured interview instrument collected the most important and in-depth information by referring to them. The criterion was the realization of theoretical saturation, which was finally conducted in 14 semi-structured interviews. Interpretive analysis using actual coding and theoretical coding was applied to analyze the content of the interviews. The reliability of the interviews was achieved through reviewing and modifying the findings and confirming the coding of each interview by the interviewee. The reliability of the interviews was confirmed by exploiting process audit and intra-subject agreement of 72%. Findings: 48 opportunities were identified in hosting the 2022 FIFA World Cup in Qatar in 6 categories: "political" with six factors, "economic" with 8, "socio-cultural" with 9, "sports industry" with 8, "Infrastructure and services" with 12 and "environment" with 4. Conclusion: By examining the opportunities of holding the mega event of the World Cup in Qatar, it is suggested to the sports administrators of the countries to host sports events to be seen on the world stage and to give international prestige to their country, increasing soft power and diplomatic influence. On the other hand, by holding international events, countries may get huge investments and partnerships with multinational companies. Tourism, however, is booming in the country, and it causes modernization, the development of technology, and job creation in key sectors such as construction, real estate, and hospitality. By holding mega sports events, however, countries may share their culture and values with the world and create a good global image for themselves. Additionally, sporting talents are discovered and championed in different sports fields while mega sports events are held.